The reform to the criminal justice in Chile: Evaluation and challenges - (:unkn) unknown (My University, 2016)
In this article we will explore the process of legal reform which has begun to transform the administration of justice in Chile. Responding to a long-standing urge to reform, and after several years of negotiations, the reformation of the code of criminal justice began in earnest on December 16, 2000, in the form of pilot programs in several regions throughout the country. These pilot programs provide a unique opportunity to test the new process.